Porphyrinic metal-organic framework/macroporous carbon composites for electrocatalytic applications - Yin, D.; Liu, Jian; Bo, X.; Li, M.; Guo, L. (Pergamon, 2017)
© 2017 Elsevier Ltd In this work, a novel porphyrinic metal-organic framework-based composite has been successfully synthesized by a simple one-step solvothermal method through growing Zr-PorMOF on macroporous carbon (MPC). Porphyrin-base MOFs combining the structural adjustable of MOFs and the specific catalytic activity of biomimetic catalysts play an important role in electrocatalysis. A series of characterization show that the roles of MPC as follow: (1) MPC could avoid the agglomeration of Zr-PorMOF particles and increase the specific surface area; (2) MPC could improve the electrochemical stability of Zr-PorMOF particles; (3) MPC could reduce the electron transfer resistance. Therefore, MPC plays the role of the conductive bridges to provide facile charge transport. The obtained Zr-PorMOF/MPC composites exhibit much better electrocatalytic activity for the reduction of hydrogen peroxide (H2O2) than the pristine Zr-PorMOF due to the synergy of Zr-PorMOF and MPC. This enzyme-free H2O2sensor shows two linear relationships in the ranges 0.5–137 µM (R2 = 0.991, sensitivity = 66 µA mM-1) and 137–3587 µM (R2 = 0.993, sensitivity = 16 µA mM-1), with a low over-potential at -0.2 V, a fast response time within 1 s and a low limit of detection (LOD) of 0.18 µM. Moreover, Zr-PorMOF/MPC composites were used to simultaneously detect uric acid (UA), xanthine (XA) and hypoxanthine (HX). These three substances are degradation products of purine metabolism. In addition, Zr-PorMOF/MPC composites can be used to develop multifunctional biosensors.